P136 CERTOLIZUMAB PEGOL IS EFFECTIVE IN THE MAINTENANCE OF RESPONSE IN MODERATE-SEVERE ULCERATIVE COLITIS: AN OPEN-LABEL MAINTENANCE STUDY. (18th January 2018) - Osterman, Mark T; Clark-Snustad, Kindra D; Singla, Anand; Afzali, Anita; Parrott, Susan; Lee, Scott D
Abstract: Background: Tumor necrosis factor inhibitors (TNFi) are effective treatments for ulcerative colitis (UC). The TNFi certolizumab pegol (CZP) is effective in Crohn's disease, and an open label (OL) study suggested that CZP is effective for induction of response in UC. Maintenance with CZP in UC has not been studied. This pilot study evaluated CZP effectiveness for maintenance of clinical and endoscopic response in patients (pts) with UC. Methods: Thirteen pts with moderate-severe UC (Complete Mayo Score (CMS) ≥6, endoscopic subscore ≥2) previously treated with OL induction CZP 400 mg subcutaneous (SC) at weeks (wks) 0, 2, 4 and 8 received OL maintenance CZP 400 mg SC every 4 wks. Pts with loss of response after wk 14 underwent dose optimization of CZP to 400 mg SC every 2 wks. Assessments include CMS, Inflammatory Bowel Disease Questionnaire (IBDQ), C-reactive protein (CRP) and safety. The primary endpoint was clinical response at wk 54. Secondary endpoints were clinical remission and endoscopic improvement at wk 54. Results: Key pt characteristics are described in Table 1. Thirteen pts received maintenance dosing: 9 entered the maintenance phase in clinical response and 4 in partial response. Twelve pts underwent dose optimization. Seven pts completed the study through wk 54, 6 discontinued early (1 inadequate response, 3 secondary non-response, 1 withdrawal of consent, 1 recurrent C. difficile). Six pts were in clinical response at wk 54, 3 were in clinical remission, and 4 had endoscopic Mayo score of 0 or 1. Six pts reported serious adverse events (7 disease exacerbations, 1 abdominal pain, 1 underwent elective colectomy). Conclusions: Effectiveness of maintenance CZP in UC in this OL study is supported by response in 46.2% and endoscopic remission in 30.8% of pts at 1 year. No new safety concerns were observed. CZP was also effective and safe for patients with prior TNFi exposure. Further randomized, placebo-controlled clinical trials are warranted.